Theatre City: On Design in the Interplay of Social and Material Space (Teatro Oficina, Bixiga, São Paulo) - Stevens, Jeroen (Culture and Local Governance / Culture et gouvernance locale, 2015)
Cultural mapping reflects a spatial turn broadly taken in related areas of urban studies, all of which, in different ways, care about the interaction between social and material space. This article will contribute to this emerging interdisciplinary field by exploring applications of cultural mapping as tools for more inclusive forms of urbanism. The main argument holds that particular forms of cultural mapping can help bridge certain constraints of ethnographic methodologies of social sciences, on one hand, and spatial analysis and design methodologies, on the other hand, as they can operate in the same interstices of social and material space. This article is the result of a three-year and ongoing collaboration between the Research Group on Urbanism and Architecture of the University of Leuven and theatre company Teatro Oficina, located on a highly contested urban site in São Paulo’s central neighbourhood of Bixiga, which for thirty years has been part and parcel of a Lute Urbaine (‘urban battle’) between the cultural group and a major real estate development firm. Both the theatre building and the surrounding terrain present themselves as pars-pro-toto for a theatrical city paradigm, offering insights on the dialectic vicissitudes of socio-cultural actions vis-à-vis the material transformation of the city.